2020
DOI: 10.1177/0271678x20921973
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion and blood–brain barrier assessment in brain trauma using contrast-enhanced near-infrared spectroscopy with indocyanine green: A review

Abstract: Contrast-enhanced near-infrared spectroscopy (NIRS) with indocyanine green (ICG) can be a valid non-invasive, continuous, bedside neuromonitoring tool. However, its usage in moderate and severe traumatic brain injury (TBI) patients can be unprecise due to their clinical status. This review is targeted at researchers and clinicians involved in the development and application of contrast-enhanced NIRS for the care of TBI patients and can be used to design future studies. This review describes the methods develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 98 publications
(135 reference statements)
0
21
0
Order By: Relevance
“…Ecological and long-term recordings of electrical and hemodynamic brain activity together with the evaluation of neurovascular coupling could allow diagnosis and monitoring of acute and chronic diseases that influence brain status and cerebrovascular health (e.g., epilepsy, stroke, vascular dementia, Alzheimer's Disease) [8,[64][65][66]. Such a neuroimaging tool can also be employed during intensive care and surgery [67][68][69][70][71][72]. Furthermore, the technology may be essential in rehabilitation protocols for studying brain plasticity and for implementing neurofeedback protocols based on brain computer interface approaches [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…Ecological and long-term recordings of electrical and hemodynamic brain activity together with the evaluation of neurovascular coupling could allow diagnosis and monitoring of acute and chronic diseases that influence brain status and cerebrovascular health (e.g., epilepsy, stroke, vascular dementia, Alzheimer's Disease) [8,[64][65][66]. Such a neuroimaging tool can also be employed during intensive care and surgery [67][68][69][70][71][72]. Furthermore, the technology may be essential in rehabilitation protocols for studying brain plasticity and for implementing neurofeedback protocols based on brain computer interface approaches [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…The passage of a bolus of contrast dye (i.e., ICG) through the brain can be monitored using NIRS [ 120 , 144 ]. The kinetic of the ICG can be related to cerebral perfusion and BBB integrity [ 120 , 144 ].…”
Section: Future Application Of Tissue Partial Oxygen Pressure and mentioning
confidence: 99%
“…The use of contrast‑enhanced NIRS would not necessarily require the measurement of absolute optical properties in the illuminated tissue and/or absolute values of physiological parameters (e.g., CBF) to assess the brain status [ 144 ].…”
Section: Future Application Of Tissue Partial Oxygen Pressure and mentioning
confidence: 99%
“…This can be explained by an impairment in cerebral autoregulation, which saw the increasing ICP cause cerebral hypoperfusion (19,20) leading to a decrease in cerebral blood volume (21) brain cells require oxygen to metabolize, the more deoxyhemoglobin is produced. Forcione et al have nicely shown how this can be done with dynamic contrast-enhanced NIRS with indocyanine green in TBI patients (25,26).…”
Section: The Changes In Relative Concentrations Ofmentioning
confidence: 99%